Flood Frequency Analysis of Feilaixia in Beijiang River Based on Empirical Mode Decomposition Reconstruction - WANG Jin; LI Xiangjiao; WANG Huan (Renmin Zhujiang)
Based on historical flood data (1764—) and measured flood data (1953—2024), the consistency of floods at Feilaixia Station in Beijiang River was tested using time series diagrams, sliding means, M-K method, and Hurst index. According to the P-III frequency analysis method, historical flood data were used to re-rank the flood series for flood frequency analysis. The frequency calculation method based on empirical mode decomposition (EMD) and synthesis was used to analyze and calculate the flood frequency. The results indicate that the extreme floods in Beijiang River have shown a trend of increasing frequency and intensity since the mid-1990s, and significant variations have occurred after testing. The flood design values for each frequency obtained using traditional hydrological frequency calculation methods increase by 500~600 m3/s compared to the original design values. By using the frequency calculation method based on EMD and synthesis, the design values of each frequency for the 2020 level year increase by more than 3 500 m3/s, and for the 2030 level year, the design values of each frequency increase by more than 3 800 m3/s. The flood frequency calculation method based on EMD reconstruction can respond to changing environments in a timely manner and has certain promotion and application value. The hydrological frequency calculation results of Feilaixia Station in Beijiang River have undergone significant changes and need to be re-evaluated as soon as possible.